Paradigma Baru: Kurikulum Baru yang Turut Mengubah Makna Guru - Alifah, Nur (Indonesian Journal Publisher, 2024)
A paradigm shift in understanding the role of teachers signifies that a teacher's responsibility goes beyond imparting knowledge to students; it also involves shaping a child's character. Teachers must be capable of guiding and directing students to reach their potential in various aspects of life. As change agents, teachers are not just educators but also mentors, motivators, and sources of inspiration for students. The research method used in this study is literature research, with data collection techniques. This research employs the literature review or literature study method. It consists of three phases: organizing the research, synchronizing results, and identifying findings in each literature review. The data analysis technique employed by the researcher is qualitative descriptive analysis. Based on the research, it can be concluded that the paradigm shift reflects a change in the mindset of the teaching approach, including changes in the role and responsibility of teachers.